Integration of Dust Hazard Research and RPE for Respiratory Health Awareness - Hardjo, Muhammad Fathur Rahman MT; Wanci, Risman; Jaya, Wiwiek Hidayati (Biology Teaching and Learning, 2025)
Abstract. This study aims to integrate research findings on dust hazard perception and compliance with Respiratory Protective Equipment (RPE) use as contextual learning in biology education. A descriptive-qualitative approach with quantitative support was applied to 141 workers in the HPAL unit of PT. X, West Sumbawa. Data on dust hazard perception and RPE compliance were collected through questionnaires and analyzed using correlation and regression tests. The results revealed a significant relationship, showing that workers with higher risk perception were six times more compliant than those with lower perception. These findings highlight the relevance of real health issues in enhancing scientific literacy, understanding of respiratory physiology, and preventive awareness in respiratory health education.Keywords: contextual learning, dust hazard perception, respiratory health, RPE compliance, scientific literacy.